Heterogenic transfusion in Italy. Historical review of a medical practice - Gorini, Ilaria; Larentis, Omar; Ciliberti, Rosagemma; Pezzoni, Barbara (Medicina Historica, 2019)
In our paper, we present a brief historical review of the transfusion practice, with a particular emphasis on the Italian research between 17th century and the end of the 19th century. Centuries of experiments, attempts and hard achievement have marked the paths toward the comprehension of the transfusion practice. The blood types discovery was possible only thanks to hundreds of attempts. In our paper, we retrace part of the work of enlightened scientists, which leads to one of the most important discovery of the last centuries.